INCREASING TEACHER PERFORMANCE THROUGH STRENGTHENING ORGANIZATIONAL CULTURE, INTERPERSONAL COMMUNICATION, AND JOB SATISFACTION: Empirical Study Using Path Analysis and SITOREM Analysis on Jakarta State Madrasah Aliyah Teachers - Nuroto Nuroto; Soewarto Hardhienata; Widodo Sunaryo (UJoST- Universal Journal of Science and Technology, 2023)
Teacher performance is the level of success of a teacher in carry out their job duties that are supported by individual abilities and skills so as to facilitate the achievement of organizational goals, especially educational goals. Teacher performance is a set of work achieved by teachers in accordance with the standards set by the education unit with careful planning and timing.This study aims to determine: (1) the direct positive effect of organizational culture on teacher performance, (2) the direct positive influence of interpersonal communication on teacher performance, (3) the direct positive effect of job satisfaction on teacher performance, (4) the direct positive influence of organizational culture. on job satisfaction, (5) direct positive effect of interpersonal communication on job satisfaction, (6) indirect positive effect of organizational culture on performance through job satisfaction, and (7) indirect positive influence of interpersonal communication on performance through job satisfaction.This study uses the path analysis method to see the direct and indirect effects between variables and the SITOREM method to determine the order of priorities and recommendations for improvements that need to be made.The research population was 231 State Madrasah Aliyah teachers in Jakarta. The research sample was 146 respondents determined by the Slovin formula. Sampling is done by Proportional Random Sampling. The results of the path analysis (1) there is a direct positive influence of organizational culture on teacher performance of = 0.115, (2) there is a direct positive influence of interpersonal communication on teacher performance of = 0.103, (3) there is a direct positive effect of job satisfaction on teacher performance of = 0.462 , (4) there is a direct positive influence of organizational culture on job satisfaction of = 0.041, (5) there is a direct positive influence of interpersonal communication on job satisfaction of = 0.574, (6) there is an indirect positive influence of organizational culture on teacher performance through job satisfaction of = 0.019, (7) there is an indirect positive influence of interpersonal communication on teacher performance through job satisfaction of = 0.265.The results of SITOREM analysis show that there are indicators of teacher performance variables, organizational culture, interpersonal communication and job satisfaction that are prioritized for improvement, including indicators (1) work effectiveness, (2) quantity of work results, and (3) work productivity, (4) Personal interest, (5) High salary amount, (6) Enjoy working together, (7) Clarity of career path, (8) Trust, (9) Positive attitude, (10) Supportive attitude, (11) Adaptable, ( 12) Information sharing, (13) Dominant values, (14) Values ​​adhered to, (15) Rules, (16) Norms and standards of behavior, and (17) Ceremonies